NUEVAS OBRAS DEL PINTOR FEDERICO MAURICIO RAMOS - Ramallo Asensio, Germán (Imafronte, 1993)
We take up again the subject of a paper addressed to the 2nd. Spanish Congress on History of Art, the Proceedings of which remain unpublished, where we briefly studied the late 19th century Murcian painter Federico Mauricio Ramos, and presented the final sketch for his painting on the ceiling of the city Theater of Romea. Now we bring up new data on him and his biography, as well as his sketch for the front curtain of the theater, finally not carried out, and a big portrait of the King Alfonso the Thirteenth signed and dated in 1902, year of the King’s majority. The portrait shows a full-length, life-sized figure and represents a step ahead both in the artist’s aesthetical evolution and in relation ro rhe old-fashioned dominant tendency in the city portrait-painring. We point out the painter’s devotion to Velázquez and Goya, and the translation of in to most of his works.